The Role of p53 as the Guardian of the Genome and the Consequences of its Mutation in Cancer Development: A Review - Purwitasari, Made Santi; Sewoyo, Palagan Senopati; Astawa, I Nyoman Mantik (Universitas Syiah Kuala, 2025)
The TP53 gene encodes the p53 protein, often referred to as the guardian of the genome due to its critical role in maintaining genomic stability and preventing tumorigenesis. Under normal conditions, p53 expression is tightly regulated by MDM2 and MDMX, which promote its degradation through ubiquitination. In response to endogenous or exogenous stress, this ubiquitination process is inhibited, leading to the stabilization of p53. Once stabilized, p53 forms a tetrameric complex in the nucleus and binds to DNA. It then activates the transcription of genes involved in cell cycle arrest, DNA repair, apoptosis, and senescence, aiming either to repair DNA damage or eliminate cells when the damage is irreparable. Nearly half of all cancer cases involve mutations in the TP53 gene. These mutations may include missense, nonsense, inframe, and splice-site mutations. Mutations in TP53 result in the production of mutant p53 (mutp53) proteins. These mutations can lead to a loss of tumor suppressor function or confer gain-of-function properties that promote tumor progression. Given its central role in cancer development, TP53 is considered a promising therapeutic target. Potential strategies include reactivating suppressed p53, restoring the function of mutp53, or inducing its degradation.